module Data.Int.Order where
Ordering integers🔗
The usual partial order on the integers relies on the observation that the number line looks like two copies of the natural numbers, smashed end-to-end at the number zero. This is precisely the definition of the order we use:
data _≤_ : Int → Int → Type where neg≤neg : ∀ {x y} → y Nat.≤ x → negsuc x ≤ negsuc y pos≤pos : ∀ {x y} → x Nat.≤ y → pos x ≤ pos y neg≤pos : ∀ {x y} → negsuc x ≤ pos y
instance ≤-neg-neg : ∀ {x y} ⦃ p : y Nat.≤ x ⦄ → negsuc x ≤ negsuc y ≤-neg-neg ⦃ p ⦄ = neg≤neg p ≤-pos-pos : ∀ {x y} ⦃ p : x Nat.≤ y ⦄ → pos x ≤ pos y ≤-pos-pos ⦃ p ⦄ = pos≤pos p ≤-neg-pos : ∀ {x y} → negsuc x ≤ pos y ≤-neg-pos = neg≤pos
Note the key properties: the ordering between negative numbers is reversed, and every negative number is smaller than every positive number. This means that decomposes, as an order, into an ordinal sum
Basic properties🔗
Proving that this is actually a partial order is a straightforward combination of case-bashing and appealing to the analogous properties for the ordering on natural numbers.
¬pos≤neg : ∀ {x y} → pos x ≤ negsuc y → ⊥ ¬pos≤neg () ≤-is-prop : ∀ {x y} → is-prop (x ≤ y) ≤-is-prop (neg≤neg p) (neg≤neg q) = ap neg≤neg (Nat.≤-is-prop p q) ≤-is-prop (pos≤pos p) (pos≤pos q) = ap pos≤pos (Nat.≤-is-prop p q) ≤-is-prop neg≤pos neg≤pos = refl ≤-refl : ∀ {x} → x ≤ x ≤-refl {x = pos x} = pos≤pos Nat.≤-refl ≤-refl {x = negsuc x} = neg≤neg Nat.≤-refl ≤-refl' : ∀ {x y} → x ≡ y → x ≤ y ≤-refl' {pos x} {pos y} p = pos≤pos (Nat.≤-refl' (pos-injective p)) ≤-refl' {pos x} {negsuc y} p = absurd (pos≠negsuc p) ≤-refl' {negsuc x} {pos y} p = absurd (negsuc≠pos p) ≤-refl' {negsuc x} {negsuc y} p = neg≤neg (Nat.≤-refl' (negsuc-injective (sym p))) ≤-trans : ∀ {x y z} → x ≤ y → y ≤ z → x ≤ z ≤-trans (neg≤neg p) (neg≤neg q) = neg≤neg (Nat.≤-trans q p) ≤-trans (neg≤neg p) neg≤pos = neg≤pos ≤-trans (pos≤pos p) (pos≤pos q) = pos≤pos (Nat.≤-trans p q) ≤-trans neg≤pos (pos≤pos x) = neg≤pos ≤-antisym : ∀ {x y} → x ≤ y → y ≤ x → x ≡ y ≤-antisym (neg≤neg p) (neg≤neg q) = ap negsuc (Nat.≤-antisym q p) ≤-antisym (pos≤pos p) (pos≤pos q) = ap pos (Nat.≤-antisym p q) unpos≤pos : ∀ {x y} → pos x ≤ pos y → x Nat.≤ y unpos≤pos (pos≤pos p) = p unneg≤neg : ∀ {x y} → negsuc x ≤ negsuc y → y Nat.≤ x unneg≤neg (neg≤neg p) = p apos≤apos : ∀ {x y} → x Nat.≤ y → assign pos x ≤ assign pos y apos≤apos {x} {y} p = ≤-trans (≤-refl' (assign-pos x)) (≤-trans (pos≤pos p) (≤-refl' (sym (assign-pos y)))) unapos≤apos : ∀ {x y} → assign pos x ≤ assign pos y → x Nat.≤ y unapos≤apos {x} {y} p = unpos≤pos (≤-trans (≤-refl' (sym (assign-pos x))) (≤-trans p (≤-refl' (assign-pos y))))
Totality🔗
The ordering on the integers is decidable, and moreover it is a total order. We show weak totality: if then
≤-is-weakly-total : ∀ x y → ¬ (x ≤ y) → y ≤ x ≤-is-weakly-total (pos x) (pos y) p = pos≤pos $ Nat.≤-is-weakly-total x y (p ∘ pos≤pos) ≤-is-weakly-total (pos x) (negsuc y) p = neg≤pos ≤-is-weakly-total (negsuc x) (pos y) p = absurd (p neg≤pos) ≤-is-weakly-total (negsuc x) (negsuc y) p = neg≤neg $ Nat.≤-is-weakly-total y x (p ∘ neg≤neg) instance Dec-≤ : ∀ {x y} → Dec (x ≤ y) Dec-≤ {pos x} {pos y} with holds? (x Nat.≤ y) ... | yes p = yes (pos≤pos p) ... | no ¬p = no λ { (pos≤pos p) → ¬p p } Dec-≤ {negsuc x} {negsuc y} with holds? (y Nat.≤ x) ... | yes p = yes (neg≤neg p) ... | no ¬p = no λ { (neg≤neg p) → ¬p p } Dec-≤ {pos x} {negsuc y} = no ¬pos≤neg Dec-≤ {negsuc x} {pos y} = yes neg≤pos
Universal properties of maximum and minimum🔗
This case bash shows that maxℤ
and minℤ
satisfy their universal properties.
maxℤ-≤l : (x y : Int) → x ≤ maxℤ x y maxℤ-≤l (pos x) (pos y) = pos≤pos (Nat.max-≤l x y) maxℤ-≤l (pos _) (negsuc _) = ≤-refl maxℤ-≤l (negsuc _) (pos _) = neg≤pos maxℤ-≤l (negsuc x) (negsuc y) = neg≤neg (Nat.min-≤l x y) maxℤ-≤r : (x y : Int) → y ≤ maxℤ x y maxℤ-≤r (pos x) (pos y) = pos≤pos (Nat.max-≤r x y) maxℤ-≤r (pos _) (negsuc _) = neg≤pos maxℤ-≤r (negsuc _) (pos _) = ≤-refl maxℤ-≤r (negsuc x) (negsuc y) = neg≤neg (Nat.min-≤r x y) maxℤ-univ : (x y z : Int) → x ≤ z → y ≤ z → maxℤ x y ≤ z maxℤ-univ _ _ _ (pos≤pos x≤z) (pos≤pos y≤z) = pos≤pos (Nat.max-univ _ _ _ x≤z y≤z) maxℤ-univ _ _ _ (pos≤pos x≤z) neg≤pos = pos≤pos x≤z maxℤ-univ _ _ _ neg≤pos (pos≤pos y≤z) = pos≤pos y≤z maxℤ-univ _ _ _ neg≤pos neg≤pos = neg≤pos maxℤ-univ _ _ _ (neg≤neg x≥z) (neg≤neg y≥z) = neg≤neg (Nat.min-univ _ _ _ x≥z y≥z) minℤ-≤l : (x y : Int) → minℤ x y ≤ x minℤ-≤l (pos x) (pos y) = pos≤pos (Nat.min-≤l x y) minℤ-≤l (pos _) (negsuc _) = neg≤pos minℤ-≤l (negsuc _) (pos _) = ≤-refl minℤ-≤l (negsuc x) (negsuc y) = neg≤neg (Nat.max-≤l x y) minℤ-≤r : (x y : Int) → minℤ x y ≤ y minℤ-≤r (pos x) (pos y) = pos≤pos (Nat.min-≤r x y) minℤ-≤r (pos _) (negsuc _) = ≤-refl minℤ-≤r (negsuc _) (pos _) = neg≤pos minℤ-≤r (negsuc x) (negsuc y) = neg≤neg (Nat.max-≤r x y) minℤ-univ : (x y z : Int) → z ≤ x → z ≤ y → z ≤ minℤ x y minℤ-univ _ _ _ (pos≤pos x≥z) (pos≤pos y≥z) = pos≤pos (Nat.min-univ _ _ _ x≥z y≥z) minℤ-univ _ _ _ neg≤pos neg≤pos = neg≤pos minℤ-univ _ _ _ neg≤pos (neg≤neg y≤z) = neg≤neg y≤z minℤ-univ _ _ _ (neg≤neg x≤z) neg≤pos = neg≤neg x≤z minℤ-univ _ _ _ (neg≤neg x≤z) (neg≤neg y≤z) = neg≤neg (Nat.max-univ _ _ _ x≤z y≤z)
Compatibility with the structure🔗
The last case bash in this module will establish that the ordering on integers is compatible with the successor, predecessor, and negation. Since addition is equivalent to iterated application of the successor and predecessor, we get as a corollary that addition also respects the order.
suc-≤ : ∀ x y → x ≤ y → sucℤ x ≤ sucℤ y suc-≤ (pos x) (pos y) (pos≤pos p) = pos≤pos (Nat.s≤s p) suc-≤ (negsuc zero) (pos y) p = pos≤pos Nat.0≤x suc-≤ (negsuc zero) (negsuc zero) p = ≤-refl suc-≤ (negsuc zero) (negsuc (suc y)) (neg≤neg ()) suc-≤ (negsuc (suc x)) (pos y) p = neg≤pos suc-≤ (negsuc (suc x)) (negsuc zero) p = neg≤pos suc-≤ (negsuc (suc x)) (negsuc (suc y)) (neg≤neg (Nat.s≤s p)) = neg≤neg p pred-≤ : ∀ x y → x ≤ y → predℤ x ≤ predℤ y pred-≤ posz posz p = ≤-refl pred-≤ posz (possuc y) p = neg≤pos pred-≤ (possuc x) posz (pos≤pos ()) pred-≤ (possuc x) (possuc y) (pos≤pos (Nat.s≤s p)) = pos≤pos p pred-≤ (negsuc x) posz p = neg≤neg Nat.0≤x pred-≤ (negsuc x) (possuc y) p = neg≤pos pred-≤ (negsuc x) (negsuc y) (neg≤neg p) = neg≤neg (Nat.s≤s p) rotℤ≤l : ∀ k x y → x ≤ y → rotℤ k x ≤ rotℤ k y rotℤ≤l posz x y p = p rotℤ≤l (possuc k) x y p = suc-≤ _ _ (rotℤ≤l (pos k) x y p) rotℤ≤l (negsuc zero) x y p = pred-≤ _ _ p rotℤ≤l (negsuc (suc k)) x y p = pred-≤ _ _ (rotℤ≤l (negsuc k) x y p) abstract +ℤ-preserves-≤l : ∀ k x y → x ≤ y → (k +ℤ x) ≤ (k +ℤ y) +ℤ-preserves-≤l k x y p = transport (sym (ap₂ _≤_ (rot-is-add k x) (rot-is-add k y))) (rotℤ≤l k x y p) +ℤ-preserves-≤r : ∀ k x y → x ≤ y → (x +ℤ k) ≤ (y +ℤ k) +ℤ-preserves-≤r k x y p = transport (ap₂ _≤_ (+ℤ-commutative k x) (+ℤ-commutative k y)) (+ℤ-preserves-≤l k x y p) negℤ-anti : ∀ x y → x ≤ y → negℤ y ≤ negℤ x negℤ-anti posz posz x≤y = x≤y negℤ-anti posz (possuc y) _ = neg≤pos negℤ-anti (possuc x) (possuc y) (pos≤pos (Nat.s≤s x≤y)) = neg≤neg x≤y negℤ-anti (negsuc _) posz _ = pos≤pos Nat.0≤x negℤ-anti (negsuc _) (possuc y) _ = neg≤pos negℤ-anti (negsuc x) (negsuc y) (neg≤neg x≤y) = pos≤pos (Nat.s≤s x≤y) negℤ-anti-full : ∀ x y → negℤ y ≤ negℤ x → x ≤ y negℤ-anti-full posz (pos y) _ = pos≤pos Nat.0≤x negℤ-anti-full posz (negsuc y) (pos≤pos ()) negℤ-anti-full (possuc x) (possuc y) (neg≤neg x≤y) = pos≤pos (Nat.s≤s x≤y) negℤ-anti-full (negsuc x) (pos y) _ = neg≤pos negℤ-anti-full (negsuc x) (negsuc y) (pos≤pos (Nat.s≤s y≤x)) = neg≤neg y≤x *ℤ-cancel-≤r : ∀ {x y z} ⦃ _ : Positive x ⦄ → (y *ℤ x) ≤ (z *ℤ x) → y ≤ z *ℤ-cancel-≤r {possuc x} {y = pos y} {pos z} ⦃ pos _ ⦄ p = pos≤pos (Nat.*-cancel-≤r (suc x) (unapos≤apos p)) *ℤ-cancel-≤r {possuc x} {y = pos y} {negsuc z} ⦃ pos _ ⦄ p = absurd (¬pos≤neg (≤-trans (≤-refl' (sym (assign-pos (y * suc x)))) p)) *ℤ-cancel-≤r {possuc x} {y = negsuc y} {pos z} ⦃ pos _ ⦄ p = neg≤pos *ℤ-cancel-≤r {possuc x} {y = negsuc y} {negsuc z} ⦃ pos _ ⦄ p = neg≤neg (Nat.*-cancel-≤r (suc x) (Nat.+-reflects-≤l (z * suc x) (y * suc x) x (unneg≤neg p))) *ℤ-preserves-≤r : ∀ {x y} z ⦃ _ : Positive z ⦄ → x ≤ y → (x *ℤ z) ≤ (y *ℤ z) *ℤ-preserves-≤r {pos x} {pos y} (possuc z) ⦃ pos z ⦄ p = apos≤apos {x * suc z} {y * suc z} (Nat.*-preserves-≤r x y (suc z) (unpos≤pos p)) *ℤ-preserves-≤r {negsuc x} {pos y} (possuc z) ⦃ pos z ⦄ p = ≤-trans neg≤pos (≤-refl' (sym (assign-pos (y * suc z)))) *ℤ-preserves-≤r {negsuc x} {negsuc y} (possuc z) ⦃ pos z ⦄ p = neg≤neg (Nat.+-preserves-≤l (y * suc z) (x * suc z) z (Nat.*-preserves-≤r y x (suc z) (unneg≤neg p))) *ℤ-nonnegative : ∀ {x y} → 0 ≤ x → 0 ≤ y → 0 ≤ (x *ℤ y) *ℤ-nonnegative {pos x} {pos y} (pos≤pos p) (pos≤pos q) = ≤-trans (pos≤pos Nat.0≤x) (≤-refl' (sym (assign-pos (x * y)))) positive→nonnegative : ∀ {x} → Positive x → 0 ≤ x positive→nonnegative (pos x) = pos≤pos Nat.0≤x -ℕ-nonnegative : ∀ {x y} → y Nat.≤ x → 0 ≤ (x ℕ- y) -ℕ-nonnegative {x} {y} Nat.0≤x = pos≤pos Nat.0≤x -ℕ-nonnegative {suc x} {suc y} (Nat.s≤s p) = -ℕ-nonnegative p -ℤ-nonnegative : ∀ {x y} → 0 ≤ x → 0 ≤ y → y ≤ x → 0 ≤ (x -ℤ y) -ℤ-nonnegative {posz} {posz} (pos≤pos p) (pos≤pos q) (pos≤pos r) = pos≤pos Nat.0≤x -ℤ-nonnegative {possuc x} {posz} (pos≤pos p) (pos≤pos q) (pos≤pos r) = pos≤pos Nat.0≤x -ℤ-nonnegative {possuc x} {possuc y} (pos≤pos p) (pos≤pos q) (pos≤pos r) = -ℕ-nonnegative (Nat.≤-peel r)
The strict order🔗
data _<_ : Int → Int → Type where pos<pos : ∀ {x y} → x Nat.< y → pos x < pos y neg<pos : ∀ {x y} → negsuc x < pos y neg<neg : ∀ {x y} → y Nat.< x → negsuc x < negsuc y instance H-Level-< : ∀ {x y n} → H-Level (x < y) (suc n) H-Level-< = prop-instance λ where (pos<pos x) (pos<pos y) → ap pos<pos (Nat.≤-is-prop x y) neg<pos neg<pos → refl (neg<neg x) (neg<neg y) → ap neg<neg (Nat.≤-is-prop x y) <-not-equal : ∀ {x y} → x < y → x ≠ y <-not-equal (pos<pos p) q = Nat.<-not-equal p (pos-injective q) <-not-equal neg<pos q = negsuc≠pos q <-not-equal (neg<neg p) q = Nat.<-not-equal p (negsuc-injective (sym q)) <-irrefl : ∀ {x y} → x ≡ y → ¬ (x < y) <-irrefl p q = <-not-equal q p <-weaken : ∀ {x y} → x < y → x ≤ y <-weaken (pos<pos x) = pos≤pos (Nat.<-weaken x) <-weaken neg<pos = neg≤pos <-weaken (neg<neg x) = neg≤neg (Nat.<-weaken x) <-asym : ∀ {x y} → x < y → ¬ (y < x) <-asym (pos<pos x) (pos<pos y) = Nat.<-asym x y <-asym (neg<neg x) (neg<neg y) = Nat.<-asym x y ≤-strengthen : ∀ {x y} → x ≤ y → (x ≡ y) ⊎ (x < y) ≤-strengthen (neg≤neg x) with Nat.≤-strengthen x ... | inl x=y = inl (ap negsuc (sym x=y)) ... | inr x<y = inr (neg<neg x<y) ≤-strengthen (pos≤pos x) with Nat.≤-strengthen x ... | inl x=y = inl (ap pos x=y) ... | inr x<y = inr (pos<pos x<y) ≤-strengthen neg≤pos = inr neg<pos <-from-≤ : ∀ {x y} → x ≤ y → x ≠ y → x < y <-from-≤ x≤y x≠y with ≤-strengthen x≤y ... | inl x=y = absurd (x≠y x=y) ... | inr p = p <-dec : ∀ x y → Dec (x < y) <-dec (pos x) (pos y) with Nat.≤-dec (suc x) y ... | yes x<y = yes (pos<pos x<y) ... | no ¬x<y = no λ { (pos<pos x<y) → ¬x<y x<y } <-dec (pos x) (negsuc y) = no λ () <-dec (negsuc x) (pos y) = yes neg<pos <-dec (negsuc x) (negsuc y) with Nat.≤-dec (suc y) x ... | yes y<x = yes (neg<neg y<x) ... | no ¬y<x = no λ { (neg<neg y<x) → ¬y<x y<x } instance Dec-< : ∀ {x y} → Dec (x < y) Dec-< {x} {y} = <-dec x y ≤-from-not-< : ∀ {x y} → ¬ x < y → y ≤ x ≤-from-not-< {pos x} {pos y} ¬x<y = pos≤pos (Nat.≤-from-not-< x y (λ x<y → ¬x<y (pos<pos x<y))) ≤-from-not-< {pos x} {negsuc y} ¬x<y = neg≤pos ≤-from-not-< {negsuc x} {pos y} ¬x<y = absurd (¬x<y neg<pos) ≤-from-not-< {negsuc x} {negsuc y} ¬x<y = neg≤neg (Nat.≤-from-not-< y x (λ y<x → ¬x<y (neg<neg y<x))) <-linear : ∀ {x y} → ¬ x < y → ¬ y < x → x ≡ y <-linear {x} {y} ¬x<y ¬y<x = ≤-antisym (≤-from-not-< ¬y<x) (≤-from-not-< ¬x<y) <-split : ∀ x y → (x < y) ⊎ (x ≡ y) ⊎ (y < x) <-split x y with <-dec x y ... | yes x<y = inl x<y ... | no ¬x<y with <-dec y x ... | yes y<x = inr (inr y<x) ... | no ¬y<x = inr (inl (<-linear ¬x<y ¬y<x)) <-trans : ∀ {x y z} → x < y → y < z → x < z <-trans (pos<pos p) (pos<pos q) = pos<pos (Nat.<-trans _ _ _ p q) <-trans neg<pos (pos<pos q) = neg<pos <-trans (neg<neg p) neg<pos = neg<pos <-trans (neg<neg p) (neg<neg q) = neg<neg (Nat.<-trans _ _ _ q p) <-≤-trans : ∀ {x y z} → x < y → y ≤ z → x < z <-≤-trans p q with ≤-strengthen q ... | inl y=z = subst₂ _<_ refl y=z p ... | inr y<z = <-trans p y<z ≤-<-trans : ∀ {x y z} → x ≤ y → y < z → x < z ≤-<-trans p q with ≤-strengthen p ... | inl x=y = subst₂ _<_ (sym x=y) refl q ... | inr x<y = <-trans x<y q abstract nat-diff-<-possuc : ∀ k x → (k ℕ- x) < possuc k nat-diff-<-possuc zero zero = pos<pos (Nat.s≤s Nat.0≤x) nat-diff-<-possuc zero (suc x) = neg<pos nat-diff-<-possuc (suc k) zero = pos<pos Nat.≤-refl nat-diff-<-possuc (suc k) (suc x) = <-trans (nat-diff-<-possuc k x) (pos<pos Nat.≤-refl) nat-diff-<-pos : ∀ k x → (k ℕ- suc x) < pos k nat-diff-<-pos zero zero = neg<pos nat-diff-<-pos zero (suc x) = neg<pos nat-diff-<-pos (suc k) zero = pos<pos auto nat-diff-<-pos (suc k) (suc x) = nat-diff-<-possuc k (suc x) negsuc-<-nat-diff : ∀ k x → negsuc k < (x ℕ- k) negsuc-<-nat-diff zero zero = neg<pos negsuc-<-nat-diff zero (suc x) = neg<pos negsuc-<-nat-diff (suc k) zero = neg<neg auto negsuc-<-nat-diff (suc k) (suc x) = <-trans (neg<neg auto) (negsuc-<-nat-diff k x) negsuc-≤-nat-diff : ∀ k x → negsuc k ≤ (x ℕ- suc k) negsuc-≤-nat-diff zero zero = neg≤neg Nat.0≤x negsuc-≤-nat-diff zero (suc x) = neg≤pos negsuc-≤-nat-diff (suc k) zero = neg≤neg auto negsuc-≤-nat-diff (suc k) (suc x) = ≤-trans (neg≤neg Nat.≤-ascend) (negsuc-≤-nat-diff k x) nat-diff-preserves-<r : ∀ k {x y} → y Nat.< x → (k ℕ- x) < (k ℕ- y) nat-diff-preserves-<r zero {suc zero} {zero} (Nat.s≤s Nat.0≤x) = neg<pos nat-diff-preserves-<r zero {suc (suc x)} {zero} (Nat.s≤s p) = neg<pos nat-diff-preserves-<r zero {suc (suc x)} {suc y} (Nat.s≤s p) = neg<neg p nat-diff-preserves-<r (suc k) {suc x} {zero} (Nat.s≤s p) = nat-diff-<-possuc k x nat-diff-preserves-<r (suc k) {suc x} {suc y} (Nat.s≤s p) = nat-diff-preserves-<r k {x} {y} p nat-diff-preserves-<l : ∀ k {x y} → x Nat.< y → (x ℕ- k) < (y ℕ- k) nat-diff-preserves-<l zero {zero} {suc y} (Nat.s≤s p) = pos<pos (Nat.s≤s Nat.0≤x) nat-diff-preserves-<l zero {suc x} {suc y} (Nat.s≤s p) = pos<pos (Nat.s≤s p) nat-diff-preserves-<l (suc k) {zero} {suc y} (Nat.s≤s Nat.0≤x) = negsuc-<-nat-diff k y nat-diff-preserves-<l (suc k) {suc x} {suc y} (Nat.s≤s p) = nat-diff-preserves-<l k {x} {y} p +ℤ-preserves-<r : ∀ x y z → x < y → (x +ℤ z) < (y +ℤ z) +ℤ-preserves-<r x y (pos z) (pos<pos p) = pos<pos (Nat.+-preserves-<r _ _ z p) +ℤ-preserves-<r (negsuc x) (pos y) (pos z) neg<pos = let rem₁ : z Nat.≤ y + z rem₁ = Nat.≤-trans (Nat.+-≤l z y) (Nat.≤-refl' (Nat.+-commutative z y)) in <-≤-trans (nat-diff-<-pos z x) (pos≤pos rem₁) +ℤ-preserves-<r x y (pos z) (neg<neg p) = nat-diff-preserves-<r z (Nat.s≤s p) +ℤ-preserves-<r x y (negsuc z) (pos<pos p) = nat-diff-preserves-<l (suc z) p +ℤ-preserves-<r (negsuc x) (pos y) (negsuc z) neg<pos = let rem₁ : suc z Nat.≤ suc (x + z) rem₁ = Nat.≤-trans (Nat.+-≤l (suc z) x) (Nat.≤-refl' (ap suc (Nat.+-commutative z x))) in <-≤-trans (neg<neg rem₁) (negsuc-≤-nat-diff z y) +ℤ-preserves-<r x y (negsuc z) (neg<neg p) = neg<neg (Nat.s≤s (Nat.+-preserves-<r _ _ z p)) +ℤ-preserves-<l : ∀ x y z → x < y → (z +ℤ x) < (z +ℤ y) +ℤ-preserves-<l x y z p = subst₂ _<_ (+ℤ-commutative x z) (+ℤ-commutative y z) (+ℤ-preserves-<r x y z p) +ℤ-preserves-< : ∀ x y x' y' → x < y → x' < y' → (x +ℤ x') < (y +ℤ y') +ℤ-preserves-< x y x' y' p q = <-trans (+ℤ-preserves-<r x y x' p) (+ℤ-preserves-<l x' y' y q) *ℤ-cancel-<r : ∀ {x y z} ⦃ _ : Positive x ⦄ → (y *ℤ x) < (z *ℤ x) → y < z *ℤ-cancel-<r {x} {y} {z} yx<zx = <-from-≤ (*ℤ-cancel-≤r {x} {y} {z} (<-weaken yx<zx)) λ y=z → <-irrefl (ap (_*ℤ x) y=z) yx<zx *ℤ-cancel-<l : ∀ {x y z} ⦃ _ : Positive x ⦄ → (x *ℤ y) < (x *ℤ z) → y < z *ℤ-cancel-<l {x} {y} {z} xy<xz = *ℤ-cancel-<r {x} {y} {z} (subst₂ _<_ (*ℤ-commutative x y) (*ℤ-commutative x z) xy<xz) *ℤ-preserves-<r : ∀ {x y} z ⦃ _ : Positive z ⦄ → x < y → (x *ℤ z) < (y *ℤ z) *ℤ-preserves-<r {x} {y} z x<y = <-from-≤ (*ℤ-preserves-≤r {x} {y} z (<-weaken x<y)) λ xz=yz → <-irrefl (*ℤ-injectiver z x y (positive→nonzero auto) xz=yz) x<y negℤ-anti-< : ∀ {x y} → x < y → negℤ y < negℤ x negℤ-anti-< {posz} {pos y} (pos<pos (Nat.s≤s p)) = neg<pos negℤ-anti-< {possuc x} {pos y} (pos<pos (Nat.s≤s p)) = neg<neg p negℤ-anti-< {negsuc x} {posz} neg<pos = pos<pos (Nat.s≤s Nat.0≤x) negℤ-anti-< {negsuc x} {possuc y} neg<pos = neg<pos negℤ-anti-< {negsuc x} {negsuc y} (neg<neg p) = pos<pos (Nat.s≤s p) negℤ-anti-full-< : ∀ {x y} → negℤ x < negℤ y → y < x negℤ-anti-full-< {x} {y} p = subst₂ _<_ (negℤ-negℤ y) (negℤ-negℤ x) (negℤ-anti-< p)